ACOUSTIC EMISSION DIRECTIVITY PATTERN OF THE COAXIAL PROPELLER FAN - Усенко, В. Ю. (Science-based technologies, 2019)
The problem of further aircraft noise abatement is one of the priority issues in civil aviation. In order to improve engine efficiency, the coaxial propellers (propeller fans) may be used. The review of literature sources shows that parameters of the propeller fan have an effect on directivity of acoustic emission of the propeller fan. The objective of this work is the assessment of increased clearance effect between rows of propellers of the coaxial propeller fans on intensity and directivity of acoustic emission of the propeller fan. The engine with two row coaxial propeller fan has been selected as the object. Diameter of the propeller fan is 4.5 m. There is base and modified propeller fan addressed in the work. The work includes acoustic emission patterns for base and modified propeller fan made by research results. The acoustic emission pattern illustrates change of acoustic power when increasing a distance between rows of propeller fan. The peaks of directivity characteristic of total emission exist in backward semi-sphere in the direction of 110º-150º. Based on the results of numerical simulation of the air flow in base propeller fan it is demonstrated that in the inlet of second row of propeller fan there is high level of air distortion. The research results of intensity and directivity of acoustic emission of the coaxial propeller fan shows that the air distortion in the inlet of second row of propeller fan is an additional source of acoustic emission into the backward semi-sphere. When increasing axial clearance between rows of propeller fan by 300 mm, the total acoustic power is reduced by 2.5 — 4.6 dB in the backward semi-sphere. In future it is planned to assess acoustic characteristics of the propeller fan when changing geometry of the second row of the propeller.